Amonização do feno de Brachiaria decumbens com diferentes teores de umidade - Reis, R. A. (1993)
The experiment was carried out to evaluate the effects of two moisture levels (18-20% and 13-15%) and three anhydrous ammonia levels (0.0; 1.5; 3.0% of NH3) on the quality of Brachiaria decumbens Stapf hay. The hay was bailed in April and weighed and treated under plastic cover during 30 days. The hay presented a similar chemical composition when bailed with high or low moisture. The percentages of NDF (80.59; 77.61; 76.10%); hemicellulose (32.56; 29.48; 28.76%) and lignin (9.53; 8.21; 7.54% decreased and the percentages of crude protein (4.04; 11.35; 13.22%) and IVDMD (36.78; 49.72; 54.33%) increased as the NH3 level increased. The fractions ADF, cellulose, and ADIN did not change due to the ammoniation. The incidence of fungi decreased with application of NH3 being the better results obtained with the 1.5% treatments.